Self-Reports of English Majors in New Licensure Examination Competencies as Basis for an In-House Review - Magalong, Mark Allen M (ASEAN Multidisciplinary Research Journal, 2022)
Competence in the licensure examination depicts a good performance. In lieu of the competencies in the new table of specifications of the licensure examination for teachers in English, this study examined the preparedness of alumni and currently enrolled students (n=142) in the College of Teacher Education in Pangasinan State University - Lingayen Campus, Philippines. Salient findings reveal that these students have 80% level of competence in all the competencies of the new TOS. Further, literature-related subjects were rated highest by these alumni and enrolled students. Comparing the alumni and enrolled students in their level of competency, the alumni showed higher competence. The researcher concluded that there are challenges brought by the pandemic in terms of teaching that affected the students’ competence. With this, the study recommends a draft in-house review program to aid the alumni and currently enrolled students in preparing for the licensure examinations.